2021
DOI: 10.20527/jwm.v9i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Daya Saing Industri Kreatif Unggulan Sulawesi Utara Menghadapi Masyarakat Ekonomi Asean (Mea)

Abstract: In 2015, Indonesia entered a new economic era in the Southeast Asian Region, namely the introduction to the Asean Economic Community (AEC). The role of the creative industry that is so large and significant must be maintained to be able to compete in the implementation of the AEC. This study aims to identify and recommend strategies for the creative and leading industries of North Sulawesi Province to improve competitiveness in the face of the AEC. To formulate alternative strategies to increase industrial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research conducted by Putong (2021), found a crisis of skilled and professional workers in the pottery and stilt house industries. The current workforce needs to be made simpler.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Putong (2021), found a crisis of skilled and professional workers in the pottery and stilt house industries. The current workforce needs to be made simpler.…”
Section: Introductionmentioning
confidence: 99%